Prominent elevation of extracellular matrix molecules in intracerebral hemorrhage - Li, Hongmin; Ghorbani, Samira; Zhang, Ruiyi; Ebacher, Vincent; Stephenson, Erin L.; Keough, Michael B.; Yong, V. Wee; Xue, Mengzhou (Frontiers in Molecular Neuroscience, 2023)
Background Intracerebral hemorrhage (ICH) is the predominant type of hemorrhagic stroke with high mortality and disability. In other neurological conditions, the deposition of extracellular matrix (ECM) molecules is a prominent obstacle for regenerative processes and an enhancer of neuroinflammation. Whether ECM molecules alter in composition after ICH, and which ECM members may inhibit repair, remain largely unknown in hemorrhagic stroke. Methods The collagenase-induced ICH mouse model and an autopsied human ICH specimen were investigated for expression of ECM members by immunofluorescence microscopy. Confocal image z-stacks were analyzed with Imaris 3D to assess the association of immune cells and ECM molecules. Sections from a mouse model of multiple sclerosis were used as disease and staining controls. Tissue culture was employed to examine the roles of ECM members on oligodendrocyte precursor cells (OPCs). Results Among the lectican chondroitin sulfate proteoglycan (CSPG) members, neurocan but not aggrecan, versican-V1 and versican-V2 was prominently expressed in perihematomal tissue and lesion core compared to the contralateral area in murine ICH. Fibrinogen, fibronectin and heparan sulfate proteoglycan (HSPG) were also elevated after murine ICH while thrombospondin and tenascin-C was not. Confocal microscopy with Imaris 3D rendering co-localized neurocan, fibrinogen, fibronectin and HSPG molecules to Iba1+ microglia/macrophages or GFAP+ astrocytes. Marked differentiation from the multiple sclerosis model was observed, the latter with high versican-V1 and negligible neurocan. In culture, purified neurocan inhibited adhesion and process outgrowth of OPCs, which are early steps in myelination in vivo. The prominent expression of neurocan in murine ICH was corroborated in human ICH sections. Conclusion ICH caused distinct alterations in ECM molecules. Among CSPG members, neurocan was selectively upregulated in both murine and human ICH. In tissue culture, neurocan impeded the properties of oligodendrocyte lineage cells. Alterations to the ECM in ICH may adversely affect reparative outcomes after stroke.